2021
DOI: 10.3390/nu13082768
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Fatty Acid Transporter FABP1 and Increased Isoprostanes and Neuroprostanes in the Human Term Placenta: Implications for Inflammation and Birth Weight in Maternal Pre-Gestational Obesity

Abstract: The rise in prevalence of obesity in women of reproductive age in developed and developing countries might propagate intergenerational cycles of detrimental effects on metabolic health. Placental lipid metabolism is disrupted by maternal obesity, which possibly affects the life-long health of the offspring. Here, we investigated placental lipid metabolism in women with pre-gestational obesity as a sole pregnancy complication and compared it to placental responses of lean women. Open profile and targeted lipido… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…This was not confirmed by our data, despite the fact that all women in the GDM group were overweight/obese. This observation was consistent with findings from our previous study, which showed that placentas from pregnant people with pre-gestational obesity did not present signs of lipid accumulation (33) . Therefore, our data indicate that obesity, whether aggravated or not by GDM, is not associated with increased placental lipid accumulation in well-controlled cohorts of women receiving nutritional counselling and insulin therapy.…”
Section: Discussionsupporting
confidence: 93%
“…This was not confirmed by our data, despite the fact that all women in the GDM group were overweight/obese. This observation was consistent with findings from our previous study, which showed that placentas from pregnant people with pre-gestational obesity did not present signs of lipid accumulation (33) . Therefore, our data indicate that obesity, whether aggravated or not by GDM, is not associated with increased placental lipid accumulation in well-controlled cohorts of women receiving nutritional counselling and insulin therapy.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, one can expect maternal dyslipidemia in obese women to alter the lipid composition of the placenta itself. Surprisingly, various studies have not revealed any differences in placental total lipid content or lipoprotein lipase mRNA expression between obese and nonobese women [61][62][63]. Nevertheless, it has been reported that maternal obesity was associated with (i) low placental FATP1 mRNA expression and a low proportion of saturated FAs in the placenta from obese women, (ii) low placental FABP1 mRNA expression and an elevated placental content of polyunsaturated free FAs, and (iii) elevated FA translocase FAT/CD36 mRNA expression and thus a higher placental content of long-chain polyunsaturated FAs, which have essential structural and functional roles in fetal development [61,63].…”
Section: Fatty Acids (Fas)mentioning
confidence: 99%
“…This may promote atherogenesis in the placental vessels (associated with pre‐eclampsia) and disrupt steroid hormone production. Obesity impacts upon fatty acid transport by the placenta and promotes an inflammatory response 111 . The capacity of the placenta to store fatty acids is limited with obesity, resulting in greater mobilisation into the foetal compartment 112 …”
Section: Mechanistic Perspectives On Programming By Obesitymentioning
confidence: 99%
“…Obesity impacts upon fatty acid transport by the placenta and promotes an inflammatory response. 111 The capacity of the placenta to store fatty acids is limited with obesity, resulting in greater mobilisation into the foetal compartment. 112 Clues with respect to the mechanism of programming by maternal obesity may be gained from studies of GDM because the long-term health of offspring exposed to GDM is largely the same as that observed with maternal obesity, although obesity can occur without GDM and vice versa.…”
Section: Mechanistic Perspectives On Programming By Obesitymentioning
confidence: 99%